FGF19 and FGF21: In NASH we trust - Saswata Talukdar; Alexei Kharitonenkov (Elsevier, 2021)
Objective: FGF19 and FGF21 have shown therapeutic promise since their discovery, attested by the fact there are at least 5 assets that activate the FGFR/KLB pathway and one FGF19 analog in clinical development. Methods: We performed a detailed analyses of published preclinical and clinical data to offer insights into the mechanism of action, as well as PK/PD and efficacy data of the clinical assets. Results: Scouring the literature, we offer mechanistic insights from preclinical data using rodents and non-human primates and pharmacodynamic data from clinical studies. Conclusion: The basic and applied science around endocrine FGFs has evolved exponentially over the years with FGF19 and FGF21 analogs are now entering Phase 3 clinical research.